On Powellithecidae fam. nov., a new Pliocene to Recent bryozoan family endemic to New Zealand, with the description of Powellitheca gen. nov. (Bryozoa, Cheilostomata) - Emanuela Di Martino; Paul D. Taylor; Dennis P. Gordon; Lee Hsiang Liow (European Journal of Taxonomy, 2016)
A new cheilostome bryozoan genus, Powellitheca gen. nov., is erected here for three species from New Zealand, one of which has been previously assigned to Emballotheca Levinsen, 1909, but which differ significantly from the Australian type species of Emballotheca, E. quadrata (MacGillivray, 1880). Notably, whereas Emballotheca has a cormidial orifice (i.e., formed by numerous neighbouring zooids), and lepralielliform ooecia, the orifice of Powellitheca gen. nov. is formed by single zooids and ooecia are of the microporelliform type. The introduction of a new family, Powellithecidae fam. nov., becomes necessary because of the nonconformity of Powellitheca gen. nov. with other known families having microporelliform ooecia. In addition to the Recent type species Powellitheca terranovae gen. et sp. nov., one other new Recent species, P. labiosa gen. et sp. nov., and a Plio-Pleistocene fossil species, Monoporella waipukurensis Waters, 1887, are assigned to the new genus.